Association of Physician Adenoma Detection Rates With Postcolonoscopy Colorectal Cancer - Schottinger, Joanne E; Jensen, Christopher D; Ghai, Nirupa R; Chubak, Jessica; Lee, Jeffrey K; Kamineni, Aruna; Halm, Ethan A; Sugg-Skinner, Celette; Udaltsova, Natalia; Zhao, Wei K; Ziebell, Rebecca A; Contreras, Richard; et al. (JAMA : the journal of the American Medical Association, 2022)
Although colonoscopy is frequently performed in the United States, there is limited evidence to support threshold values for physician adenoma detection rate as a quality metric. To evaluate the association between physician adenoma detection rate values and risks of postcolonoscopy colorectal cancer and related deaths. Retrospective cohort study in 3 large integrated health care systems (Kaiser Permanente Northern California, Kaiser Permanente Southern California, and Kaiser Permanente Washington) with 43 endoscopy centers, 383 eligible physicians, and 735 396 patients aged 50 to 75 years who received a colonoscopy that did not detect cancer (negative colonoscopy) between January 2011 and June 2017, with patient follow-up through December 2017. The adenoma detection rate of each patient's physician based on screening examinations in the calendar year prior to the patient's negative colonoscopy. Adenoma detection rate was defined as a continuous variable in statistical analyses and was also dichotomized as at or above vs below the median for descriptive analyses. The primary outcome (postcolonoscopy colorectal cancer) was tumor registry-verified colorectal adenocarcinoma diagnosed at least 6 months after any negative colonoscopy (all indications). The secondary outcomes included death from postcolonoscopy colorectal cancer. Among 735 396 patients who had 852 624 negative colonoscopies, 440 352 (51.6%) were performed on female patients, median patient age was 61.4 years (IQR, 55.5-67.2 years), median follow-up per patient was 3.25 years (IQR, 1.56-5.01 years), and there were 619 postcolonoscopy colorectal cancers and 36 related deaths during more than 2.4 million person-years of follow-up. The patients of physicians with higher adenoma detection rates had significantly lower risks for postcolonoscopy colorectal cancer (hazard ratio [HR], 0.97 per 1% absolute adenoma detection rate increase [95% CI, 0.96-0.98]) and death from postcolonoscopy colorectal cancer (HR, 0.95 per 1% absolute adenoma detection rate increase [95% CI, 0.92-0.99]) across a broad range of adenoma detection rate values, with no interaction by sex (P value for interaction = .18). Compared with adenoma detection rates below the median of 28.3%, detection rates at or above the median were significantly associated with a lower risk of postcolonoscopy colorectal cancer (1.79 vs 3.10 cases per 10 000 person-years; absolute difference in 7-year risk, -12.2 per 10 000 negative colonoscopies [95% CI, -10.3 to -13.4]; HR, 0.61 [95% CI, 0.52-0.73]) and related deaths (0.05 vs 0.22 cases per 10 000 person-years; absolute difference in 7-year risk, -1.2 per 10 000 negative colonoscopies [95%, CI, -0.80 to -1.69]; HR, 0.26 [95% CI, 0.11-0.65]). Within 3 large community-based settings, colonoscopies by physicians with higher adenoma detection rates were significantly associated with lower risks of postcolonoscopy colorectal cancer across a broad range of adenoma detection rate values. These findings may help inform recommended targets for colonoscopy quality measures.